Frequency of chromosome 22q11.2 deletion among newborns with non-syndromic congenital heart defects from western Mexico - Gerardo E. Fabián-Morales; Lucina Bobadilla-Morales; Christian Peña-Padilla; Rafael Nieto-García; Pascuala B. Rivera-Ramírez; Alfredo Corona-Rivera; Aurea Márquez-Mora; Graciela Macías-Salcedo; Idalid Cuero-Quezada; Jorge R. Corona-Rivera (Permanyer, 2022)
Background: Congenital heart defects (CHD) are among the most frequent manifestations of 22q11.2 deletion syndrome. Although we found relatively few studies aimed at specifically detecting 22q11.2 deletion in newborns (NB) with CHD, none of them has been performed in Mexico. Methods: We conducted a prospective hospital-based study from January 2017 to March 2021 in the Genetics and Pediatric Cardiology Services of the Hospital Civil de Guadalajara Dr. Juan I. Menchaca (Guadalajara, Mexico). All consecutive NBs identified with any non-syndromic major CHD confirmed by echocardiography were eligible to participate. A total of 98 NBs were included, 51 males and 47 females. Fluorescence in situ hybridization (FISH) analysis was conducted to search for deletion of chromosome 22q11.2 in interphase nuclei of standard lymphocyte cultures. Results: We found eight patients (8.2%) with CHD and the 22q11.2 deletion, all of them with conotruncal defects, particularly of the truncus arteriosus (p = 0.013), tetralogy of Fallot (p = 0.024), and pulmonary atresia with ventricular septal defect (p = 0.031) subtypes. With de exception of one infant with hypocalcemia and another with hypocalcemia and thymic aplasia, the diagnosis of 22q11.2 deletion was not clinically suspected in the other patients. Conclusions: Our results confirm the importance of excluding the presence of the 22q11.2 deletion in every NB with CHDs, particularly of the conotruncal subtype, even in the absence of other manifestations.